Ответы и объяснения

Лучший Ответ!
2013-05-06T13:41:44+00:00

 s/ t = 3/2  значит t /s = 2/3

 

 a) (-2t)/(3s)+1 = (-2/3)*(2/3)+1 = 5/9

 

b)  (s/t-2.5)^2 +t/s = (1.5-2.5)^2+2/3 = 1+2/3=5/3

 

c) разделим числитель и знаменатель на s :

 

    (2t/s-3s/s)/(3t/s+2s/s) = (2*2/3-3)/(3*2/3+2) = (4/3-3)/(2+2) = (-5/3)/4 = -5/12

 

d)  1)   s>0   t>0

       

        ( | s/1.5 | - s) / ( | s/1.5 |+s) = (s/1.5-s)/(s/1.5+s) = (s-1.5s)/(s+1.5s) = (1-1.5)/(1+1.5)= -0.5/2.5 = -1/5

      

      2)   s<0   t<0

 

       ( | s/1.5 | + s) / ( | s/1.5 |-s) = (-s/1.5+s)/(-s/1.5-s) = (-s+1.5s)/(-s-1.5s) = (-1+1.5)/(-1-1.5) = 0.5/(-2.5) = -1/5